ANALYSIS OF SYARI'AH ACCOUNTING IN MURABAHAH FINANCING AT THE SYARI'AH MANDIRI BANK IN JAMBI BRANCH - Mukhzarudfa Mukhzarudfa; Muhammad Qodri (ILTIZAM Journal of Shariah Economics Research, 2020)
This study intends to find out the murabahah financing procedure and analyze the murabahah financing accounting system implemented at the Jambi SyariahMandiri Bank Branch. In this study analyzing data with a qualitative descriptive approach, and collected by doing documentary studies, observations and interviews. This study concludes that the general procedure for submitting murabahah financing to Bank SyariahMandiri in four ways, the first is to propose a letter of intent to use murabahah financing products, the second is to analyze the ability to pay installments, goodwill and collateral, the third is approving proposals and fourth is to execute a murabahah contract. Meanwhile, the Islamic accounting system applied in Bank SyariahMandiri uses a sigma system which is useful for recording murabahah financing. An accounting system is a system that includes several forms, both in the form of journals, procedures, and tools used to process financial accounts. This analysis supports the murabahah accounting system in Islamic banking. Then, compare the records of financial transactions with PSAK 59